The Medieval chronicle.
1 online resource (288 pages)
Keywords: Alongside annals, chronicles were the main genre of historical writing in the Middle Ages. Their significance as sources for the study of medieval history and culture is today widely recognised not only by historians, but also by students of medieval literature and linguistics and by art historians. The series The Medieval Chronicle aims to provide a representative survey of the on-going research in the field of chronicle studies, illustrated by examples from specific chronicles from a wide variety of countries, periods and cultural backgrounds. There are several reasons why the chronicle is particularly suited as the topic of a yearbook. In the first place there is its ubiquity: all over Europe and throughout the Middle Ages chronicles were written, both in Latin and in the vernacular, and not only in Europe but also in the countries neighbouring on it, like those of the Arabic world. Secondly, all chronicles raise such questions as by whom, for whom, or for what purpose were they written, how do they reconstruct the past, what determined the choice of verse or prose, or what kind of literary influences are discernable in them. Finally, many chronicles have been beautifully illuminated, and the relation between text and image leads to a wholly different set of questions. The Medieval Chronicle is published in cooperation with the Medieval Chronicle Society (medievalchronicle.org).